Salivary metals, age, and gender correlate with cultivable oral Candida carriage levels. Issue 1 (1st January 2018) - Norris, Hannah L.; Friedman, Justin; Chen, Ziqiang; Puri, Sumant; Wilding, Gregory; Edgerton, Mira
ABSTRACT: Background : Little is known about the normal range of metal levels in unstimulated saliva, nor whether these might impact Candida carriage in healthy individuals. Both are important in determining which populations are at risk for candidiasis, as the availability of metal ions can influence the growth and pathogenesis of Candida albicans . Objective : We quantified salivary metals of healthy individuals to determine the correlation with C. albicans oral colonization. Design : Unstimulated whole saliva was collected from healthy adults and plated to determine fungal carriage, and metal content was measured using ICP-mass spectrometry (ICP-MS). Results : Zinc was most abundant, followed by iron, copper, manganese, and nickel. Cultivable oral Candida carriage was found in 48% of people. Total protein levels did not differ in salivas from donors with or without carriage. However, innate fungicidal activity was increased in donors with carriage; correlations between levels of several metals were stronger in salivas with fungal carriage, indicating a shift in the oral environment. Concentrations of copper and manganese, as well as age and gender, were significantly predictive of carriage levels in a multiple regression model. Conclusions : Salivary copper and manganese content along with age and gender could be used as a predictive metric for individuals that are more susceptible to Candida overgrowth.